The “Metropolitan City” in Italy: New Spaces for Dialogue and Interaction Between the City and the Mountain - Federica Corrado; Erwin Durbiano (Revue de Géographie Alpine)
The mountain areas live a period of new dynamism, in which the connection with the urban context has an important role in terms of cultural redesign of values, physical and functional connections with the local areas and creation of urban-mountain interactions. The article focuses on Italian mountain system, comprising experimentation and excellence, but even rupture and depopulation perspectives, in which the city and mountain are no longer simply the borders of an entre-deux (“between two”, Bourdeau 2015) relationship.The article taking into consideration the current direction of Metropolitan Cities, the newborn institutions established as an intermediate level in local governance. The new Metropolitan Cities were officially born in 2014, following the approval of Law n° 56 “Disposizioni sulle città metropolitane, sulle province, sulle unioni e fusioni di comuni” (Provisions concerning metropolitan cities, provinces, and unions/fusions between townships). Metropolitan Cities are defined as wide-scale local entities and they are institutional body with task of planning and local development government, in many cases regarding urban and mountain territories.The article proposes a wide range of situations in which forms of strategic planning for the systemization of city-mountain relationships has been adopted. At first level, it has been considered Strategic plans that give formal indication about the exchange between urban and mountain areas. Three significant cases: the Piano Strategico della città e del territorio di Cuneo 2020 (2020 Strategic plan for the city of Cuneo and its surroundings mountain areas); the Piano Strategico territoriale della Provincia di Belluno (Strategic plan for the mountain-urban area of Belluno); and the Piano Strategico Metropolitano di Bologna 2020 (2020 Strategic plan for the metropolitan city of Bologna and its surroundings mountain area ).At second level the analysis regards the initiatives carried out by the Aosta Valley region (the Strategic Plan for Aosta) and the experience of the “Piano Strategico dei Comuni dell’Alto Canavese” (Strategic Plan for the townships in the Alpine upper Canavese area, within the Metropolitan City of Turin). Wide areas in which the actors have experimented a strategic planning in order to create strong interactions between urban and mountain context through a process of local governance.The results of the analysis permit to highlight some issues: the definition of mutual benefit between city and mountain context; the construction of a strategic polycentric vision inside the urban-mountain territories; concerns inter-territoriality as a tool to build metropolitan identity.